Implementasi Sarana dan Prasarana Perpustakaan SMPN 1 Sirah Pulau Padang Terhadap Pengaruh Minat Kunjungan Siswa - Dita Oktaviana; Rani Kurnia Vlora (Perpustakaan Universitas Riau, 2025)
Information is a vital resource essential for continuous living and the teaching-learning process, with the library as one of its primary providers. School libraries play an integral role in supporting the curriculum and fostering a culture of literacy among students. However, low visiting interest in some cases is often associated with the sub-optimal implementation of facilities and infrastructure. This research aims to analyze and describe the implementation of facilities and infrastructure at the SMP Negeri 1 Sirah Pulau Padang Library and identify its influence on student visiting interest. This study employed a qualitative research approach, utilizing data collection techniques such as direct observation, interviews, and documentation. The research location was SMP N 1 Sirah Pulau Padang, Ogan Komering Ilir Regency. The findings indicate that the implementation of physical facilities and infrastructure is reasonably adequate, featuring a spacious room, good arrangement, and basic amenities that support comfort. A key deficiency was found in the lack of technological facilities (computers) for reference searching. The crucial finding of this research is that the non-physical factor, namely the quality of human resources (HR) and excellent service provided by competent and friendly librarians, proved to be a significant driver of student visiting interest. The implementation of facilities and infrastructure, well-managed by the right HR, resulted in a high visitation rate, reaching approximately 30 students per day. It is concluded that comprehensive implementation of facilities and infrastructure, supported by outstanding librarian service quality, creates a comfortable environment and successfully increases student visiting interest.